Self Efficacy Memediasi Pengaruh Pengetahuan Kewirausahaan, Teaching Factory, dan Penggunaan Media Sosial terhadap Minat Berwirausaha (Universitas Negeri Semarang, 2022)
This study aims to examine and analyze the effect of entrepreneurial knowledge, teaching factory, use of social media on entrepreneurial interest through self efficacy. The unit of analysis in this study is the interest in entrepreneurship in the students of SMK NU 01 Kendal. In this study, the entire population was used as the unit of analysis. The data collection method in this study used a questionnaire. The data analysis technique used is descriptive analysis, regression analysis, path analysis and sobel test. The result showed that: 1) entrepreneurial knowledge, teaching factory, use of social media, and self efficacy affect interest in entrepreneurship, 2) entrepreneurial knowledge, teaching factory, and use of social media affect self efficacy, 3) self efficacy cannot mediate the effect of knowledge entrepreneurship, teaching factory, the use of social media on the interest in entrepreneurship.